Kualitas Hidup Lansia Pengguna Gigi Tiruan di Desa Toulimembet Kecamatan Kakas - Worang, Veren T.; Siagian, Krista V.; Tendean, Lydia E. N. (Universitas Sam Ratulangi, 2019)
Abstract: Good quality of life is very desirable for elderly to fulfill a meaningful, happy, and useful life. The loss of whole or partial teeth has the same effect as disability. Well-made artificial teeth can improve mastication, pronunciation, as well as aesthetic function, maintain healthy tissue, and prevent further damage to the structures in oral cavity. This study was aimed to determine the quality of life of elderly denture users at Desa Toulimembet, Kakas. This was a descriptive study with a cross sectional design. Population consisted of elderly denture users as many as 195 people meanwhile samples were obtained by using purposive sampling techniques. The instrument used in this study was GOHAI questionnaire. The results showed that there were 77 elderly denture users in this study. The assessment of quality of life based on the dimensions of physical function, namely limiting the amount of food, experiencing problems when chewing, and difficulty, was categorized as quite good; based on the dimensions of pain and discomfort which were taking drugs to relieve pain, felt uncomfortable, and was sensitive to food were classified as quite good category; and based on the dimensions of psychosocial aspects namely limiting oneself, being anxious or worried, and feeling insecurity was classified as quite good category. Generally, the assessment of quality of life based on the three dimensions was quite good. In conclusion, the quality of life of elderly denture users at Desa Toulimembet, Kakas was quite good.Keywords: denture users, elderly, quality of lifeÂ Abstrak: Kualitas hidup yang baik merupakan sesuatu yang sangat diinginkan lansia agar dapat menikmati masa tuanya dengan penuh makna, membahagiakan, dan berguna. Hilangnya seluruh gigi atau sebagian berefek yang sama dengan kecacatan hidup. Gigi tiruan diharapkan dapat memperbaiki fungsi pengunyahan, pengucapan, estetis, menjaga kesehatan jaringan serta mencegah kerusakan lebih lanjut dari struktur organ dalam rongga mulut. Penelitian ini bertujuan untuk mengetahui kualitas hidup lansia pengguna gigi tiruan di Desa Toulimembet Kecamatan Kakas. Jenis penelitian ialah deskriptif dengan desain potong lintang. Populasi penelitian ialah lansia pengguna gigi tiruan sebanyak 195. Responden berjumlah 77 lansia diperoleh dengan teknik purposive sampling. Instrumen yang digunakan ialah kuesioner GOHAI. Hasil penelitian menunjukkan bahwa penilaian kualitas hidup berdasarkan dimensi fungsi fisik yaitu, membatasi jumlah makanan, mengalami masalah saat mengunyah dan kesulitan tergolong kategori cukup baik; dimensi nyeri dan ketidaknyamanan yaitu mengonsumsi obat-obatan untuk menghilangkan nyeri, merasa tidak nyaman dan sensitif terhadap makanan tergolong kategori cukup baik; serta dimensi aspek psikososial yaitu membatasi diri, cemas atau kwatir, dan tidak percaya diri tergolong kategori cukup baik. Secara keseluruhan penilaian kualitas hidup berdasarkan 3 dimensi tersebut tergolong cukup baik. Simpulan penelitian ini ialah kualitas hidup lansia pengguna gigi tiruan di Desa Toulimembet Kecamatan Kakas tergolong cukup baik.Kata kunci: Pengguna gigi tiruan, lansia, kualitas hidup